Physiological and performance characteristics of male professional road cyclists - Mujika, I.; Padilla, S. (Sports Medicine, 2001)
Male professional road cycling competitions last between 1 hour (e.g. the time trial in the World Championships) and 100 hours (e.g. the Tour de France). Although the final overall standings of a race are individual, it is undoubtedly a team sport. Professional road cyclists present with variable anthropometric values, but display impressive aerobic capacities [maximal power output 370 to 570 W, maximal oxygen uptake 4.4 to 6.4 L/min and power output at the onset of blood lactate accumulation (OBLA) 300 to 500 W]. Because of the variable anthropometric characteristics, 'specialists' have evolved within teams whose job is to perform in different terrain and racing conditions. In this respect, power outputs relative to mass exponents of 0.32 and 1 seem to be the best predictors of level ground and uphill cycling ability, respectively. However, time trial specialists have been shown to meet requirements to be top competitors in all terrain (level and uphill) and cycling conditions (individually and in a group). Based on competition heart rate measurements, time trials are raced under steady-state conditions, the shorter time trials being raced at average intensities close to OBLA (approximately 400 to 420 W), with the longer ones close to the individual lactate threshold (LT, approximately 370 to 390 W). Mass-start stages, on the other hand, are raced at low mean intensities (approximately 210 W for the flat stages, approximately 270 W for the high mountain stages), but are characterised by their intermittent nature, with cyclists spending on average 30 to 100 minutes at, and above LT, and 5 to 20 minutes at, and above OBLA.